Analysis of the vibration characteristics of a strongly coupled liquid-structure-gas system - Zainulabidin, Muhd Hafeez (2007)
This thesis describes an investigation of the vibration of a system comprising a thin elastic plate, acting as a separator, between a fluid and gas column contained in a cylindrical container. The intention is that the plate will constrain the movement of the liquid to one end of the container, preventing it from splashing around the container enclosure, hence improving the stability of the system. However in general systems involving fluid-structural vibration interaction, it has been shown by previous researchers that there exists a critical condition where the fluid and structure are strongly coupled together. At this critical condition the levels of vibration induced kinetic energy of the plate and fluid are comparable. This strong couple characteristic may affect the stability and structural health of the whole coupled system especially the thin elastic plate. In this thesis, critical vibration characteristics of such system are studied. The theoretical analysis of vibration interaction of liquid-structure-gas system is presented. The values of natural frequencies and relative energy distribution throughout the system obtained theoretically have been verified with the values obtained by finite element analysis and by laboratory experiment where appropriate. Then, the characteristics of strong coupled vibration interaction of liquid-structuregas system are investigated around three possible strong coupled conditions. Results have shown that for a liquid-structure-gas system, strong couple vibration occurs if the system fulfills either of the following conditions: